This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: = X – Y (a) (2) = (1) + (3) (b) (3) = G1(2) where G1 = 1/(τ 1 s + 1) (c) (4) Y = G2(3) where G2 = 0.5/(τ 1 s/2 + 1) (d) From (d) and (c) Y = (2)G1G2 = G1G2 (X – Y + (3) ) (e) Also from (b) and (c) (3) = G1((1) + (3)) (3)(1 – 1/(τ 1 s + 1)) = 1/(τ 1 s + 1) (3) τ 1 s = 1 (3) = 1/(τ 1 s ) = (X – Y) / (τ 1 s) Substitute this in (e) ( ) Y X s s s Y + + + = 1 1 1 1 1 ) 1 2 )( 1 ( 5 . τ 1 2 1 1 2 2 1 + + = s s X Y Q – 12.3. For the control system shown determine the transfer function C(s)/R(s)...
View
Full
Document
This note was uploaded on 11/13/2011 for the course COP 4355 taught by Professor Koslov during the Spring '10 term at University of Florida.
 Spring '10
 Koslov

Click to edit the document details